A Case Study of Parent-Child Interaction in Their Reading Activity - Bo Wang; Evan Afri (International Journal of English and Applied Linguistics (IJEAL), 2023)
Parents play an important role in the character-shaping of their children, and it is mostly processed during the parent-child interaction. Children can be deeply influenced at home in terms of mother tongue, ideology, habit, or personal behavior. Hence, parent-child reading activity has been used as a popular mode that offers an opportunity to affect children purposely. However, many parents are confused about the way to interact with their children, either verbally or not. This study tries to look into this problem by observing a real case. The conversation between a parent and a child is audio recorded, transcribed, and analyzed. The result shows that equal power distribution can be found in this particular case, and there are two identities that the child can find herself, i.e., teacher and student. In addition, the mother adopts a number of strategies to help fulfil her expectation, such as reading material selection, teaching ideological lessons, child’s language development, evoking imagination, and praising strategy. The findings may provide implications for parents who are confused about how to interact with their children properly and effectively.